Diaphyseal aneurysmal bone cyst: A case report - Reza, Faisal; Nasution, Ikhwanul Hakim (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Aneurysmal bone cyst (ABC) is benign lesion of long bone metaphysis, but it can also become locally aggressive lesion. ABC affects mostly medullary region of long bone metaphysis that predominantly affects children and young adults. Meta-diaphysis of the long bones and posterior elements of the vertebrae are the most common sites of involvement. ABCs can involve every skeletal site, but the most common locations are the metaphysis of the long bones, followed by the spine. However, diaphyseal lesions may occur. Patients with ABCs typically present with insidious onset of pain, swelling or a palpable mass. The imaging appearance of ABC is variable; however, a lytic and expansile lesion with fluid-fluid levels is the most common presentation. Although incidence of intracortical variety of ABCs is rare but surgeons might evaluate its severity in view of aggressive benign or malignant lesions of diaphysis. We present the case of a 11-year-old female with left shaft ulna ABC.